Social Studies Teachers' Perceptions of the Importance of Employing Twenty-First Century Skills in Teaching (Journal Of Educational and Psychological Researches, 2022)
The study aimed to identify the perceptions of social studies teachers in the Governorate of Muscat about the importance of employing the skills of the twenty-first century in teaching. The study employed a qualitative approach. The two researchers used an analytical approach based on the Grounded Theory, the data was gathered through semi-structured interviews with (15) male and female teachers. The results indicated that social studies teachers relate the twenty-first-century skills more to improving students’ achievement level in the subject, while they see that these skills have less influence in developing students’ communication skills and cooperation with their peers. In light of the results of the study, the two researchers recommend paying attention to the perceptions of social studies teachers of the importance of employing and enhancing the twenty-first-century skills and making use of them in improving the educational process. In addition, teachers also need to be provided with the tools and technological means that they need to continue the educational practices required in this century. Furthermore, the attention must be directed to the developers of social studies curricula to be able to integrate the skills of the twenty-first century in the curriculum of social studies.